Assessment of microbiological processes while storage of grain spring wheat - Гавриленко, О. С.; Хоміцька, О. А.; Загорулько, О. В. (Scientific Progress & Innovations, 2016)
The influence of preparation complex with composite microelement origin of the bacteria and fungi cultures,isolated from grains of spring wheat of State Enterprise Novotroitsk elevator in Kyiv region during storage was studied. We established fungicidal effectiveness of the drug, which consists of silver and copper minerals in the form of organic salts of carboxylic acids obtained through nanotechnology. The results of studies of specific pathogens of grain of winter wheat are presented.